Work organisation, human capital and innovation strategies: new evidence from firm-level Italian data - Michele Capriati; Marialuisa Divella (Global Labor Organization (GLO), 2017)
By using firm-level data provided by the fourth round of the (Italian) Community Innovation Survey (CIS 2012), this paper explores whether the implementation of specific changes in work organisation within a firm influences its innovation performance, not only directly, but also via reinforcing the link between human capital resources and innovation. The authors also analyse the overall effect of human capital and work organisation, which enables them to identify which combination of these variables leads to the highest level of firms' technological capabilities. Main findings confirm that not only the acquisition of new skills through the hiring of qualified personnel, but also how personnel management affects individual employees on the work floor should be considered to the development of firms' innovation capacity: indeed, work organisation as well as strong positive complementarities or synergy effects between human capital and work organisation have been found to give firms a clear competitive advantage vis à vis both noninnovating firms and firms unable to internally generate new products and processes (i.e. entirely or at least partly by themselves). These positive effects are present and relevant in both manufacturing and service firms, whilst a more differentiated impact has emerged between firms in high-tech and low-tech sectors of the economy. On the whole, the contribution raises some relevant issues about the Italian lack of innovation in work organisation, which requires particular attention by the human resources management of firms and the industrial policy of governments.
Keywords: O30; O31; O32; 330; work organisation; human capital; technological capabilities; innovation generation; firms; industries